Notes on the Mnemosyne Atlas: conception, critical reception, and method (Palíndromo, 2024)
The Mnemosyne Atlas, an innovative project undertaken by Aby Warburg (1866–1929) in the last years of his life, is currently the subject of growing scholarly interest. In this article, we aim to contribute to the current discussion on the atlas by offering a comprehensive historical-contextual analysis of its creation, reception, and methodological nuances. Through a critical analysis of the literature, we present two hypotheses: i) the inseparability of the Mnemosyne Atlas from the general context of Warburg’s work, i.e., its close relationship to a number of texts adjacent to it; ii) the enigmatic and seemingly arbitrary character of the atlas as a direct reflection of a style of textual production based on the formulation of aphorisms and the linking of the fragmentary as a legitimate form of theoretical reflection.
Keywords: Aby Warburg; Mnemosyne Atlas; Art Historiography; Visual Studies